Strategies for combating antibiotic resistance in bacterial biofilms - Grooters, Kayla E.; Ku, Jennifer C.; Richter, David M.; Krinock, Matthew J.; Minor, Ashley; Li, Patrick; Kim, Audrey; Sawyer, Robert; Li, Yong (Frontiers in Cellular and Infection Microbiology, 2024)
Biofilms, which are complexes of microorganisms that adhere to surfaces and secrete protective extracellular matrices, wield substantial influence across diverse domains such as medicine, industry, and environmental science. Despite ongoing challenges posed by biofilms in clinical medicine, research in this field remains dynamic and indeterminate. This article provides a contemporary assessment of biofilms and their treatment, with a focus on recent advances, to chronicle the evolving landscape of biofilm research.